Enhancement of Solubility, Dissolution, and Anti-Inflammatory Activity of Aceclofenac via Multicomponent Crystal Formation with Tromethamine - Hendrizal Usman; Salman Umar; Yufri Aldi; Muhammad Nasrul Siregar; Erizal Zaini (Fakultas Farmasi Universitas Andalas, 2026)
Aceclofenac (ACE) is a non-steroidal anti-inflammatory drug (NSAID) widely used for osteoarthritis and rheumatoid arthritis, yet its therapeutic performance is limited by poor aqueous solubility as a Biopharmaceutics Classification System (BCS) Class II drug. This study aimed to enhance the physicochemical and pharmacological properties of ACE by forming a multicomponent crystal (MC) with tromethamine (TRIS). The MC was produced via solvent-dropped grinding in a 1:1 molar ratio and characterized by differential scanning calorimetry (DSC), powder X-ray diffraction (PXRD), and Fourier-transform infrared spectroscopy (FTIR). DSC and PXRD results indicated the formation of a eutectic system with reduced crystallinity, while FTIR showed intermolecular hydrogen bonding, evidenced by the broad OH stretching band near 3000 cm⁻¹, without new covalent bond formation. Solubility increased 35.8-fold relative to pure ACE, and dissolution testing showed a markedly improved dissolution efficiency (DE₆₀) of 75.33 ± 1.57% compared with 49.10 ± 0.54% for ACE alone. In vivo anti-inflammatory assessment using a carrageenan-induced granuloma pouch model further demonstrated superior pharmacological activity of the MC, significantly reducing exudate volume (0.56 mL) and TNF-α levels (25.26 pg/mL) versus pure ACE (0.82 mL and 29.70 pg/mL). Overall, the ACE–TRIS multicomponent crystal effectively enhances solubility, dissolution, and anti-inflammatory efficacy, offering a promising approach for improving ACE’s therapeutic performance.